Haemodynamic effects of dobutamine with special reference to myocardial blood flow. A comparison with dopamine and isoprenaline. Issue 1 (July 1979) - Stephens, J; Ead, H; Spurrell, R
Abstract : The haemodynamic effects of dobutamine (2.5 to 10 micrograms/min per kg) were determined in 5 patients without cardiac failure who were undergoing cardiac catheterisation for suspected coronary disease. Myocardial blood flow was determined by the coronary sinus thermodilution technique. Data were compared with those from two groups of 5 patients who received dopamine (4-8 micrograms/min per kg) and isoprenaline (0.005-0.025 micrograms/min per kg). Each drug was given in a lower and a higher dose, and all increased mean cardiac index (dobutamine, 18% and 39%; dopamine, 11% and 23%; isoprenaline, 15% and 44%). These increases were associated with significant increases in mean myocardial oxygen consumption (dobutamine, 38% and 61%; dopamine, 25% and 62%; isoprenaline, 20% and 45%). Mean myocardial blood flow was increased by each drug but mean myocardial oxygen extraction was decreased by isoprenaline, was increased by dopamine, and was unchanged by dobutamine. Each inotropic agent has a similar effect on myocardial oxygen consumption, but isoprenaline has a direct coronary vasodilator action while dopamine has a coronary vasoconstrictor action. Dobutamine has no direct effect upon coronary vascular tone.